2017
DOI: 10.1016/j.gca.2016.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature formation and stabilization of rare allotropes of cyclooctasulfur (β-S8 and γ-S8) in the presence of organic carbon at a sulfur-rich glacial site in the Canadian High Arctic

Abstract: Large-scale deposits of elemental sulfur form annually on a glacier's surface at Borup Fiord Pass in the Canadian High Arctic. However, the mechanisms of mineralization and stabilization of elemental sulfur at this site are currently unknown. Here we show that x-ray diffraction (XRD) data for fresh sulfur precipitates collected from the surface of a melt pool over sulfide-rich ice reveal the presence of three sulfur allotropes, α-S 8 , β-S 8 , and γ-S 8 (the three solid forms of cyclooctasulfur (S 8 )). The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 48 publications
(18 reference statements)
2
47
0
Order By: Relevance
“…In addition to the cycling of sulfur identified at BFP we also searched for core metabolic processes including carbon and nitrogen metabolism. Low levels of nitrate were previously reported at BFP (0.0030 mM in 2009; Wright et al, 2013, and 0.0908 mM in 2014; Lau et al, 2017) within both spring and melt pool fluids, respectively, possibly due to microbial nitrate reduction. Based on gene presence/absence we infer that some MAGs from BFP may be capable of nitrate/nitrite reduction.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In addition to the cycling of sulfur identified at BFP we also searched for core metabolic processes including carbon and nitrogen metabolism. Low levels of nitrate were previously reported at BFP (0.0030 mM in 2009; Wright et al, 2013, and 0.0908 mM in 2014; Lau et al, 2017) within both spring and melt pool fluids, respectively, possibly due to microbial nitrate reduction. Based on gene presence/absence we infer that some MAGs from BFP may be capable of nitrate/nitrite reduction.…”
Section: Discussionmentioning
confidence: 59%
“…The spring system of interest is approximately 210-240 m above sea level and occurs at the toe of two coalesced glaciers (Grasby et al, 2003). The spring system is thought to be perennial in nature but discharges from different locations along the glacier from year to year (Grasby et al, 2003; Gleeson et al, 2010; Wright et al, 2013; Lau et al, 2017). However, given lack of winter observations it is not confirmed that spring flow is year-round or limited to the warmer spring and summer months.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an essential component of biomass, sulfur is assimilated into organic compounds and is also involved in energy yielding processes either as electron acceptor or donor in chemolithautotrophic, photolithoautotrophic and heterotrophic microorganisms (Kletzin et al, 2004;Friedrich et al, 2005;Robertson and Kuenen, 2006;Sievert et al, 2007;Finster, 2008;Dahl et al, 2008;Sievert and Vetriani, 2012). In various environments, elemental sulfur accumulates in amounts visible to the naked eye, including marine sediments, microbial mats, hydrothermal vents, glacial shields, oxygen minimum zones and volcanic soils (Ruby et al, 1981;Woodruff and Shanks, 1988;Raiswell, 1992;Taylor and Wirsen, 1997;Alonso-Azcárate et al, 2001;Engel et al, 2004;Zopfi et al, 2004;Lavik et al, 2009;Cosmidis and Templeton, 2016;Lau et al, 2017). In these cases, sulfur occurs mostly in the form of zero-valence sulfur (S 0 ) with cyclooctasulfur (S 8 ) as the most stable and common form (Steudel and Eckert, 2003).…”
Section: Introductionmentioning
confidence: 99%